Nanobodies—Useful Tools for Allergy Treatment? - Flicker, Sabine; Zettl, Ines; Tillib, Sergei V. (Frontiers in Immunology, 2020)
In the last decade single domain antibodies (nanobodies, VHH) qualified through their unique characteristics have emerged as accepted and even advantageous alternative to conventional antibodies and have shown great potential as diagnostic and therapeutic tools. Currently nanobodies find their main medical application area in the fields of oncology and neurodegenerative diseases. According to late-breaking information, nanobodies specific for coronavirus spikes have been generated these days to test their suitability as useful therapeutics for future outbreaks. Their superior properties such as chemical stability, high affinity to a broad spectrum of epitopes, low immunogenicity, ease of their generation, selection and production proved nanobodies also to be remarkable to investigate their efficacy for passive treatment of type I allergy, an exaggerated immune reaction to foreign antigens with increasing global prevalence.